Impact of cyclodextrins on the behavior of amphiphilic ligands in aqueous organometallic catalysis - Bricout, Hervé; Léonard, Estelle; Len, Christophe; Landy, David; Hapiot, Frédéric; Monflier, Eric (Beilstein Journal of Organic Chemistry, 2012)
In this study, we showed that the addition of randomly modified β-cyclodextrin (RAME-β-CD) in aqueous medium could have a beneficial impact on the catalytic performances of phosphane-based aggregates in the Pd-catalyzed cleavage of allyl carbonates (Tsuji–Trost reaction). The RAME-β-CD/phosphane supramolecular interactions helped explain the catalytic results. The presence of RAME-β-CD in the aqueous compartment improved the phosphane-based aggregate dynamics. The exchanges between the hydrophobic substrate-containing aggregate core and the catalyst-containing aqueous phase were then greatly favored, resulting in an increase in the catalytic performances.
Keywords: amphiphilic phosphanes; biphasic system; cyclodextrins; micelles

Chemistry in Alternative Reaction Media - Adams, D. J.; Dyson, P. J.; Tavener, S. J. (John Wiley & Sons, 2004)

Alternative Solvents for Green Chemistry - Kerton, F. M. (Royal Society of Chemistry, 2009)

Green Solvents – Properties and Applications in Chemistry - Mohammed, A.; Inamuddin (Springer, 2012)

(untitled) - Kuntz, E. G. (CHEMTECH, 1987)

(untitled) - Shaughnessy, K. H. (Chem. Rev., 2009)

(untitled) - Ferreira, M.; Bricout, H.; Azaroual, N.; Landy, D.; Tilloy, S.; Hapiot, F.; Monflier, E. (Adv. Synth. Catal., 2012)

(untitled) - Bricout, H.; Banaszak, E.; Len, C.; Hapiot, F.; Monflier, E. (Chem. Commun., 2010)

(untitled) - Ferreira, M.; Bricout, H.; Azaroual, N.; Gaillard, C.; Landy, D.; Tilloy, S.; Monflier, E. (Adv. Synth. Catal., 2010)

(untitled) - Cepeda, M.; Daviña, R.; García-Río, L.; Parajó, M. (Chem. Phys. Lett., 2010)

(untitled) - De Lisi, R.; Milioto, S.; Muratore, N. (J. Phys. Chem. B, 2002)

(untitled) - De Lisi, R.; Lazzara, G.; Milioto, S.; Muratore, N. (J. Phys. Chem. B, 2003)

(untitled) - De Lisi, R.; Lazzara, G.; Milioto, S.; Muratore, N.; Terekhova, I. V. (Langmuir, 2003)

(untitled) - García-Río, L.; Méndez, M.; Paleo, M. R.; Sardina, F. J. (J. Phys. Chem. B, 2007)

(untitled) - Bricout, H.; Hapiot, F.; Ponchel, A.; Tilloy, S.; Monflier, E. (Curr. Org. Chem., 2010)

(untitled) - Hapiot, F.; Ponchel, A.; Tilloy, S.; Monflier, E. (C. R. Chim., 2011)

(untitled) - Six, N.; Guerriero, A.; Landy, D.; Peruzzini, M.; Gonsalvi, L.; Hapiot, F.; Monflier, E. (Catal. Sci. Technol., 2011)

(untitled) - Hapiot, F.; Leclercq, L.; Azaroual, N.; Fourmentin, S.; Tilloy, S.; Monflier, E. (Curr. Org. Synth., 2008)